2023
DOI: 10.7759/cureus.37733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Awareness of Musculoskeletal Injuries Associated With Competitive Video Gaming in Saudi Arabia

Abstract: BackgroundIn recent years, the use of electronic devices has become an important part of the lives of adolescents who regularly use computers for academic activities and leisure. The excessive use of these devices has been associated with several health problems, such as obesity, headaches, anxiety, stress, sleep disorders, and musculoskeletal pain. This study aimed to assess the prevalence and awareness of musculoskeletal injuries associated with competitive video gaming in Saudi Arabia. MethodologyThis descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…11 Furthermore, a study of competitive video gaming in Saudi Arabia showed that the most reported sites of injuries included the lower back (63.8%), neck (50%), hand/wrist (44.8%), and shoulder (35.3%). 12 The proportion of esports athletes with physical complaints in Japan is thought to be similar to that of these previous findings, but no empirical study has been conducted.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…11 Furthermore, a study of competitive video gaming in Saudi Arabia showed that the most reported sites of injuries included the lower back (63.8%), neck (50%), hand/wrist (44.8%), and shoulder (35.3%). 12 The proportion of esports athletes with physical complaints in Japan is thought to be similar to that of these previous findings, but no empirical study has been conducted.…”
Section: Introductionmentioning
confidence: 68%
“…11 Furthermore, a study of competitive video gaming in Saudi Arabia showed that the most reported sites of injuries included the lower back (63.8%), neck (50%), hand/wrist (44.8%), and shoulder (35.3%). 12 The proportion of esports athletes with physical complaints in Japan is thought to be similar to that of these previous findings, but no empirical study has been conducted. Furthermore, differences in the proportion of those with physical complaints by attributes such as age, body size, and esports level (professional or amateur) have not been examined among esports players.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations